ANALISIS KOMPETENSI PETUGAS REKAM MEDIS TERHADAP MUTU PELAYANAN REKAM MEDIS DI RSUD BERKAH PANDEGLANG - Christin, Rumondang; Rusdiana, Ima; Rahmi, Junaida; Herawati, Aryana (EDU RMIK Jurnal Edukasi Rekam Medis Ilmu Kesehatan, 2025)
This study aims to examine the competence of medical record officers in relation to the quality of medical record services at RSUD Berkah Pandeglang. Officer competence plays a vital role in ensuring the completeness, accuracy, security, confidentiality, and availability of medical records. This research used a descriptive qualitative method with data collection through interviews and observations. The findings showed that most officers did not have an educational background in medical records but had over 10 years of work experience. Performance evaluations are conducted regularly, and most activities follow existing procedures even though a written SOP is still under development. In terms of security, access to electronic medical records (EMR) is regulated through individual accounts and reinforced through regular staff awareness campaigns. Regarding confidentiality, access is limited to healthcare personnel directly involved in patient care. In terms of completeness and accuracy, medical records are generally filled within 24 hours, although some incompleteness still occurs due to staff discipline. For availability, while no formal SOP currently exists, services continue based on existing policies such as internal decrees (SK). Based on these findings, it is recommended that the hospital expedite the development of written SOPs and conduct regular training to improve the quality of medical record services.